Regulation of hyaluronan synthesis by vasodilatory prostaglandins - Fischer, Jens W.; Schrör, Karsten (Thrombosis and Haemostasis, 2007)
Hyaluronan (HA) is a macromolecular polysaccharide of the vascular extracellular matrix that confers both structural functions as well as signalling activity. HA is involved in a wide variety of biological processes, such as tissue morphogenesis, malignant growth and metastasis, wound healing and angiogenesis. In atherosclerosis, HA associates with leukocytes and vascular smooth muscle cells (VSMC) and is involved in vascular remodelling. HA is synthesized at the plasma membrane by three HAsynthase isoforms (HAS1–3). Human VSMC upregulate HAS1 and HAS2 in response to prostaglandins via Gs-coupled prostaglandin receptor subtypes IP and EP2. This review discusses the regulation of HA-synthesis by prostaglandins and the evidence for a central role of cyclooxygenase-2/PGE2 in regulation of HAsynthesis during atherogenesis.
Keywords: Extracellular matrix; hyaluronic acid; hyaladherins; hyaluronidase; vascular smooth muscle cell; inflammation